Macrolophus pygmaeus induces systemic resistance in tomato against Meloidogyne - Alejandro Expósito; Pablo Urbaneja-Bernat; Sara Boncompte; Aida Magdalena Fullana; Ariadna Giné; Francisco Javier Sorribas; Jordi Riudavets (Scientific Reports, 2025)
Abstract The ability of Macrolophus pygmaeus to induce systemic resistance in susceptible and Mi1.2 resistant tomato against Meloidogyne spp. was evaluated in 200cm3 pot experiments. The susceptible cv. Roma and the resistant cv. Caramba were exposed to 15 M. pygmaeus nymphs per plant in mesh bags for 48 h and then were inoculated with 200 stage juveniles (J2) of M. incognita or 600 J2 of a mixed community of M. arenaria, M. hapla, and M. javanica. Tomato plants were maintained in a growth chamber during 40 days. Then the number of egg masses and eggs per plant were determined. In addition, the preference of the insect was evaluated confronting nematode-infected vs. non-infected plants in a Y-tube olfactometer and in insect cages, where 10 females were released into each cage containing resistant or susceptible tomato plants. After 1, 2, 4, 24, 48 and 72 h, the number of M. pygmaeus was counted as well as the offspring after 14 days. The infectivity and reproduction of M. incognita were reduced by 37% and 53%, respectively, in susceptible tomato plants inoculated with M. pygmaeus. Inoculation with the nematode community resulted in a 52% reduction in infectivity and a 37% reduction in reproduction. However, no effect was observed in the Mi1.2 resistant tomato plants, regardless of the nematode inoculum. The preference and the offspring of M. pygmaeus was not negatively affected by the nematode infection or the tomato cultivar. In conclusion, pre-induction of tomato plants with M. pygmaeus reduces RKN infectivity and reproduction in susceptible but not in Mi1.2 resistant tomato.